Laser frequency measurements and spectroscopic assignments of optically pumped 13CH3OH - Hockel, H.; Lauters, M.; Jackson, M.; Moraes, João Carlos Silos [UNESP]; Allen, M. D.; Evenson, K. M. (Springer, 2001)
A three-laser heterodyne system was used to measure the frequencies of twelve optically pumped laser emissions from 13CH3OH in the far-infrared (FIR) region. These emissions, ranging from 54 to 142 μm, are reported with fractional uncertainties up to ±2 × 10-7 along with their polarization relative to the CO2 pump. Using the 9P32 and 10R14 CO2 lines, complete spectroscopic assignments for two laser systems were confirmed.
Keywords: Carbon dioxide lasers; Fourier transform infrared spectroscopy; Infrared radiation; Light emission; Light polarization; Methanol; Spectroscopic analysis; Far infrared region; Llasere frequency measurements; Optically pumped laser emissions; Three laser heterodyne system; Optically pumped lasers